Improving the Methodology of Preparing Students FOR Engineering Activity - Rakhimov Sarvar Ibragimovich (Periodica Journal, 2022)
The article talks about the purposeful use of modern educational technologies and tools in the preparation of students for engineering activities, the introduction of innovative pedagogical technologies, increasing students' interests in science, having clear ideas about the performance of labor objects in practical training, and the formation of in-depth knowledge, skills and qualifications for the performance of labor operations.
Keywords: engineering; educational technologies; innovative pedagogical technologies; imagination